Evaluating social effects of arable field abandonment in communal areas of South Africa - Pokwana, Sihle (Rhodes University, Faculty of Science, Department of Environmental Science)
The phenomenon of arable field abandonment, a complex and multifaceted aspect of land use dynamics, has become a subject of increasing significance in rural landscapes. Across diverse geographic contexts, the abandonment of once-cultivated fields is indicative of transformative shifts in agricultural practices, reflecting the interplay of numerous socio-economic, environmental, and cultural factors. The abandonment of arable fields in the former homelands of the Eastern Cape and KwaZulu-Natal poses a multifaceted challenge with significant social implications. Historically, agriculture has been central to these regions, yet recent trends show a shift from traditional field cultivation to alternative practices such as garden cultivation or complete cessation. This shift has heightened vulnerability to food insecurity, hunger, and poverty, particularly as high unemployment levels exacerbate the situation. Moreover, the intricate relationships between humans and their surrounding ecosystems is also affected. Therefore, understanding the drivers of arable field abandonment at the community or household level can reveal localised factors that differ from broader, generalised drivers identified in previous studies. Additionally, examining the diverse impacts on these communities is crucial for developing targeted interventions that address their specific needs and enhance resilience. This study investigates arable field abandonment in specific villages of Gotyibeni and Melani in the Eastern Cape and Manqorholweni and Mawane, in KwaZulu-Natal. Using the Driving forces, Pressures, State, Impacts, and Responses (DPSIR) framework as a conceptual framework uncovers the driving factors, pressures, state, impacts and responses of this phenomenon in these rural villages. The study's main aim was to assess the social effects of arable field abandonment in the selected study areas. The main objective is to determine how livelihoods, social relationships, and living conditions within and between households have changed following the cessation of field cultivation. The study also employed several specific objectives: first, to identify trends in field cultivation within the study areas; second, to analyse the drivers contributing to arable field abandonment in the villages; third, to examine the impact of field abandonment on the elderly population over the past 50 years; and fourth, to investigate the level of youth engagement in agriculture, including how the abandonment of arable fields affects their participation and perceptions of agriculture as a livelihood. To achieve the objectives the study employed mixed research methods that combine satellite imagery analysis, household surveys, oral history interviews with elders, most of whom had stopped farming, and youth focus group discussions. Landsat 7 Satellite imagery with a 15-meter spatial resolution was sourced from the South African Space Agency (SANSA) for the four study areas. The temporal coverage spanned from 1972 to 2020, with considerations for image usability based on resolution. Unfortunately, many earlier images were deemed unusable due to low resolution, particularly affecting Gotyibeni, where clear images only became available from 2013, therefore for this village the focus was on two decades. Arable fields, residential areas, homestead gardens, grasslands, and shrublands were classified. Change detection utilised a post-classification approach, comparing land cover categories between the early and late 2000s. A change detection matrix and statistics were generated using a ha/year formula, enabling the quantification of land cover changes. Image analysis employed ArcGIS 10.8.1 software for mapping and classification, involving georeferencing, signature file creation, maximum likelihood classification, and conversion from raster to vector formats for area calculations. For the LULC change matrix, an intersection analysis in ArcGIS overlaid data from different time points, and a pivot table in Excel organised resulting data. A focus on arable land changes, particularly conversions to other land uses, was crucial, as the study is investigating the level of arable field abandonment in these areas, understanding how much arable land has been converted or remained unchanged provides a clear indication of the extent of abandonment. To understand driving forces of arable field abandonment, a semi-structured questionnaire was developed based on the Driving forces, Pressures, States, Impacts, and Responses (DPSIR) framework. The questionnaires were administered through household interviews conducted in the four study villages. Sections of the questionnaire covered household involvement in cropping, perceptions of land use change, abandonment of field cultivation, and socio-economic demographics. Sampling involved a random selection of 20% of total households in each village, with data analysis performed using Statistical Package for Social Sciences (SPSS). Chi-square tests and Kruskal-Wallis analysis were employed to assess differences between villages. A second questionnaire specifically targeting households that had abandoned field cultivation was also done. Ninety-seven interviews were conducted to evaluate economic, health, socio-cultural and environmental impacts from respondents that indicated to have ceased field cultivation. Data analysis through SPSS utilised descriptive statistics and chi-square tests to identify statistically significant differences between villages. Oral histories were collected from elderly individuals in each village from a sample size of 15 individuals who were previous cultivators of fields, selected with the assistance of a village leader. The selected elders provided qualitative insights into historical and contemporary experiential aspects of village life. The focus was on changes in village relations, the environment, generational values, and traditional farming practices in each village. Youth-focused group discussions were organised with 30 young people in the village between the ages of 18-35, covering topics such as youth goals, the importance of field cultivation, and perceptions of the future. Both the oral histories and focus group discussions conducted in the local languages, were tape-recorded, transcribed, and subjected to content analysis to identify and interpret themes and patterns. The approach involved coding sentences, grouping codes into sub-themes, and further organising them into categories and subcategories. The LULC change results showed a consistent trend of significant arable land reduction across all villages, accompanied by a notable increase in grassland cover. Manqorholweni experienced the most significant loss of these arable fields. This finding was further supported by the household interviews which revealed 100% abandonment of fields in this village. Grasslands emerged as the dominant land cover in all villages, overtaking arable fields and homestead gardens. Regarding field abandonment, 76% of households across villages left fields unused for over 19 years due to reasons including lack of fencing, animal damage to crops, and financial constraints, despite recognising the socio-economic importance of field cultivation. Respondents expressed interest in returning to cultivation if the state would assist with fencing materials and costs. Concerns such as loss of cultural identity due to field abandonment were raised, especially in Manqorholweni, Mawane, and Melani. Homestead gardens were identified as a compensating strategy, with 78% of respondents actively maintaining them, although LULC change results indicated a decline, except in Mawane. Field cultivation revealed gender, age, and educational disparities, with non-cropping households having more female heads, individuals above 55, and higher proportions with only primary education. Households that abandoned field cultivation reported a decline in economic stability, with 97% experiencing less stable household economic circumstances. Unemployment was prevalent, with over 70% relying on social grants, creating financial challenges for 76% lacking sufficient cash. Limited off-farm formal employment (20%) was observed, while remittances played a minor role, this resulted in insufficient monthly income, affecting 94% of respondents. Dietary diversity declined, and reliance on store-bought food led to health concerns. Field abandonment impacted family dynamics, altering power relationships and reducing interaction, also heightened by COVID-19, affecting cultural identity and community cohesion. Youth across villages were not currently engaged in field cultivation or farming but expressed interest in revitalising agriculture. They recognised the socio-economic significance of agriculture and highlighted the importance of capital, resources, and government support. Challenges for youth involvement included lack of information, absence of agricultural advisors, and disparities in access to credit. Lack of support from elders and limited sharing of agricultural knowledge further hindered youth's ability to initiate farming projects. In conclusion, this study highlights the significant issue of arable field abandonment in rural areas of the Eastern Cape and KwaZulu-Natal, reflecting broader socio-economic and environmental transformations. The consistent reduction in arable land across the studied villages, coupled with the rise in grassland cover, underscores a critical shift from traditional agricultural practices to alternative land uses. The abandonment of fields has had profound impacts on community livelihoods, leading to decreased economic stability, reduced dietary diversity, and weakened social and cultural ties. The findings reveal a clear need for targeted interventions to address the specific challenges faced by these communities, particularly regarding food security and economic resilience. To address the challenges of arable field abandonment, it is crucial to implement a multi-faceted support program. This should include providing essential resources such as fencing, irrigation systems, and agricultural tools to facilitate field cultivation. Additionally, engaging and supporting youth in agriculture through training, access to advisors, and financial aid is vital to revitalise interest in farming. Strengthening social safety nets by enhancing financial support systems can mitigate economic challenges faced by affected households. Furthermore, initiating cultural and educational programs to preserve traditional farming knowledge while integrating modern practices will help maintain cultural identity and community cohesion. These measures are key to improving resilience and livelihoods in the context of field abandonment.,Thesis (PhD) -- Faculty of Science, Environmental Science, 2025
Keywords: Arable land; Land abandonment; Livelihood; Rural conditions; Food security -- South Africa; Land cover; South Africa Economic conditions